Democracy on trial : social movements and cultural politics in postauthoritarian Taiwan - Chuang, Ya-Chung, 1965-
Writing "an ethnography of democracy," the author describes and analyzes a multifaceted Taiwanese society. Contradicting mainstream research on political cultures, which relies heavily on survey data and statistical analysis, the author produces an anthropologically inspired, contextually rich study using original source materials. He traces a genealogy of pivotal concepts, such as sovereignty, identity, and locality, at the heart of Taiwan's democratic discourse and relates the experience of democracy as "a way of life" from the viewpoints of a variety of subjects, including social movement participants, urban community members, and ethnic activists. His book explores the loaded meaning of democracy.